A bibliometric analysis of smallholder farmers’ climate change adaptation challenges: a SADC region outlook - Dumisani Shoko Kori; Walter Musakwa; Clare Kelso (International Journal of Climate Change Strategies and Management)
Purpose – This paper aims to explore pathways in which adaptation challenges may occur. Focus is on the barriers to adaptation, challenges to adaptation and maladaptation with reference to smallholder farmers in the Southern African Development Community region. Design/methodology/approach – Bibliometric analysis techniques were used to track the literature on smallholder farmers’ adaptation challenges. Web of Science was the main data source. A total of 41 articles were retained for analysis and exported into Visualization of Similarities Viewer Software where the development of research on the subject, co-occurrence of keywords analysis, top publishers, citations and total link strength was done. Findings – Results indicate that research on smallholder farmers’ adaptation challenges is not new but has gained more consideration post-2020. The main adaptation challenges emanate from perception barriers and constraints based on determinants of adoption, limitations for resilience building and achieving sustainable adaptation as well as contestations around Climate Smart Agriculture technologies. Practical implications – Effective design of adaptation policies should center on prioritizing the needs of the local people. This would reduce the occurrences of smallholder farmers’ adaptation challenges, promote resilience building and contribute toward achieving sustainable adaptation. Originality/value – It is equally important to document adaptation challenges. However, adaptation challenges are rarely shared with the same enthusiasm as its successes. This work focuses on the matter with the intention of conscientizing smallholder farmers to reduce the risk of repeating the same adaptation mistakes.